Clinicopathological characteristics of non‐B non‐C hepatocellular carcinoma without past hepatitis B virus infection. Issue 5 (24th July 2016) - Kimura, Takefumi; Kobayashi, Akira; Tanaka, Naoki; Sano, Kenji; Komatsu, Michiharu; Fujimori, Naoyuki; Yamazaki, Tomoo; Shibata, Soichiro; Ichikawa, Yuki; Joshita, Satoru; Umemura, Takeji; Matsumoto, Akihiro; et al.
Abstract : Aim: Past hepatitis B virus (HBV) infection is considered a risk factor for hepatocarcinogenesis, but the clinicopathological characteristics of non‐B non‐C hepatocellular carcinoma (NBNC‐HCC) excluding past HBV infection have not been investigated. This study aimed to clarify the clinicopathological features of strictly defined NBNC‐HCC. Methods: Among HCC patients who underwent surgical resection at our affiliated hospitals in Nagano prefecture, Japan, between 1996 and 2012, 77 were negative for serum anti‐HBV core/surface antibodies in addition to HBV surface antigen and anti‐hepatitis C virus antibody without signs of autoimmune liver disease, Wilson disease, or hemochromatosis. These patients were divided into the alcohol intake‐positive group (ethanol intake >20 g/day, n  = 31), non‐alcoholic fatty liver group (steatosis >5% and ethanol intake <20 g/day, n  = 30), and cryptogenic group (no ethanol intake or steatosis, n  = 16). Preoperative clinical parameters, tumor and background liver pathology, and prognosis were analyzed. Results: Advanced fibrosis and steatosis were detected in 64% and 60% of all patients, respectively. Approximately 85% of the alcohol intake‐positive patients had advanced fibrosis. Non‐alcoholic fatty liver HCC subjects had the highest body mass index and prevalence of diabetes, but 30–40% had none to mild fibrosis. The cryptogenic group of HCC patients had the lowest incidence of accompanying hepatic inflammation/fibrosis but the largest tumor size. Recurrence/survival rates were comparable among the groups. Conclusions: Liver fibrosis and steatosis are risk factors of HCC regardless of past HBV infection and ethanol consumption. The present results also indicate the possibility of hepatocarcinogenesis independent of hepatic steatosis, inflammation and fibrosis, ethanol intake, and past HBV infection.